NEEDS ASSESSMENT OF ADMINISTRATION MODEL FOR PHYSICAL EDUCATION COURSE IN GENERAL EDUCATION AT UBON RATCHATHANI UNIVERSITY - Tanok, Chaowanan; Phucharoen , Thongchat; Malarat, Anan (Academic Journal of Thailand National Sports University, 2019)
The current research aims to conduct needs assessment of administration for physical education course in general education at Ubon Ratchathani University. The research samples were obtained by stratified random sampling. 386 participants were students from different faculties in different years of their studies. A questionnaire was used as the main data collection tool to conduct needs assessment of administration for physical education course in general education at Ubon Ratchathani University. The data was analyzed using percentage, standard deviation, and PNI Modified analysis. Regarding the research results, it was found that, 1) the overall current state of the administration for physical education course in general education, particularly involving curriculum, personnel, assessment was found at a high level. In terms of learning and teaching management, course materials, and facilities, the overall administration was found at a moderate level. Regarding the expectation of administration for physical education course, it was found that the expectation was found at a high level in every aspect of administration, 2) it was found that teaching materials and facilities were needed most among participants (PNIb = 0.28), followed by learning management (PNIb = 0.24), curriculum design (PNIb = 0.16) personnel (PNIb = 0.12) and assessment (PNIb = 0.10) respectively.